2020
DOI: 10.1007/s00464-020-08169-0
|View full text |Cite
|
Sign up to set email alerts
|

Applying the electronic nose for pre-operative SARS-CoV-2 screening

Abstract: Background Infection with SARS-CoV-2 causes corona virus disease (COVID-19). The most standard diagnostic method is reverse transcription-polymerase chain reaction (RT-PCR) on a nasopharyngeal and/or an oropharyngeal swab. The high occurrence of false-negative results due to the non-presence of SARS-CoV-2 in the oropharyngeal environment renders this sampling method not ideal. Therefore, a new sampling device is desirable. This proof-of-principle study investigated the possibility to train machine-learning cla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 35 publications
2
49
0
1
Order By: Relevance
“…To this we provide a positive answer, providing proof of concept for VOC-based real-time detection of SARS CoV-2 infection. We note that results to this effect have also recently been obtained by others: In one study [ 28 ], the authors used a commercial metal-oxide-sensor-based eNose, albeit different from ours (Aeonose, The Aeonose Company, Zutphen, the Netherlands). They sampled oral exhaled breath from 219 participants, of which 57 were COVID-19 positive.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…To this we provide a positive answer, providing proof of concept for VOC-based real-time detection of SARS CoV-2 infection. We note that results to this effect have also recently been obtained by others: In one study [ 28 ], the authors used a commercial metal-oxide-sensor-based eNose, albeit different from ours (Aeonose, The Aeonose Company, Zutphen, the Netherlands). They sampled oral exhaled breath from 219 participants, of which 57 were COVID-19 positive.…”
Section: Discussionsupporting
confidence: 64%
“…Beyond this, the primary weakness that limits our effort to the status of proof of concept alone is the level of false positives. Although as noted our statistically significant 66.7% true positive rate (or 75.8% for non-symptomatic) is not far off of RT-PCR true positive rates [ 28 ], and we obtain this result instantaneously rather than days later, our 57% false positive rate prevents this method from deployment in its current form. Thus, our result is a basic-science proof of concept, and not a clinical tool.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Another type of e‐nose (Aeonose) was tested for its plausibility to screen out COVID‐19 positive patients before surgery. [ 72 ] This system is based on an array of three microhotplate metal oxide sensors: carbon monoxide, nitrogen dioxide, and VOC sensors that change their conductivity after exposure. The sensors operation temperature cycles between 260 and 340 °C, followed by machine learning (ML) methodology used for classifying the data, the results showing 86% sensitivity.…”
Section: Materials and Sensing Technologiesmentioning
confidence: 99%
“…Several groups have reported SARS-CoV-2 positivity in samples of exhaled breath condensate (EBC) ( 21 25 ), and based on Ct values, Ma et al further showed that EBC-positive COVID-19 patients exhaled millions of SARS-CoV-2 RNA copies per hour ( 23 ). Standard diagnosis of viruses based on swabs or serum has been rapidly developed ( 17 , 26 29 ), while auxiliary methods, such as trace biomarkers of COVID-19 in exhalations, have also been explored ( 18 20 ). Nevertheless, there is an urgent need for novel methods to detect SARS-CoV-2 in the transmission path.…”
Section: Introductionmentioning
confidence: 99%